2018
DOI: 10.1186/s12881-018-0620-y
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analyses of the relationship between glutathione S-transferase gene polymorphisms and renal cell carcinoma susceptibility

Abstract: BackgroundAssociation of GSTM1- and GSTT1-null genotypes, GSTP1 A/G gene polymorphism with renal cell carcinoma (RCC) susceptibility was detected, and the relationship between the GSTM1/GSTT1-null genotype and clinical TNM stages of RCC was assessed, using meta-analysis method.MethodsAssociation investigations according to eligibility criteria were searched and identified from the databases of Cochrane Library, PubMed, and Embase from establishment time of databases to July 1, 2017, and eligible reports were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Furthermore, polymorphisms in GST genes could affect both individual response to carcinogen exposure and pharmacogenomic-based cancer treatment (Lo and Ali-Osman 2007). So far the association of common GST gene polymorphisms (GSTM1, GSTT1, GSTP1 and GSTA1), independently or in interaction with environmental factors, with increased risk of developing RCC has been shown (Coric et al 2016;Zhong et al 2018). Novel omega class GST consists of two isoenzymes, GSTO1-1 and GSTO2-2.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, polymorphisms in GST genes could affect both individual response to carcinogen exposure and pharmacogenomic-based cancer treatment (Lo and Ali-Osman 2007). So far the association of common GST gene polymorphisms (GSTM1, GSTT1, GSTP1 and GSTA1), independently or in interaction with environmental factors, with increased risk of developing RCC has been shown (Coric et al 2016;Zhong et al 2018). Novel omega class GST consists of two isoenzymes, GSTO1-1 and GSTO2-2.…”
Section: Introductionmentioning
confidence: 99%
“…However, no changes in GST were detected in this study. A meta-analysis in 2018 reported that glutathione S-transferase gene polymorphism (GST-PI) gene mRNA was high in NSCLC and was involved in the pathogenesis and prognosis of NSCLC [36,37]. In contrast, a study reported that the levels of GSH were low in EGFR-T790M NSCLC and increased GSH expression in acquired NSCLC cells resensitized by the EGFR TKIs [38].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, GSTM1‐active genotype was confirmed to be an independent predictor of poor RCC survival . What is more, it has been shown that the GSTM1‐null genotype was associated with a lower tumor grade, whereas the GSTT1‐null genotype was associated with more advanced TNM stages (Table ) …”
Section: The Role Of Gsts In Rcc Progressionmentioning
confidence: 99%
“…57 What is more, it has been shown that the GSTM1-null genotype was associated with a lower tumor grade, whereas the GSTT1-null genotype was associated with more advanced TNM stages (Table 2). 49,56,[73][74][75] GSTO1 also possesses numerous regulatory roles, such as modulation of ryanodine receptors (RyRs), posttranslational processing of interleukin-1β (IL1-β), and proposed antiapoptotic role. [77][78][79] Furthermore, it has been suggested that GSTO1-1 could also contribute to tumor chemoresistance by activation of survival signaling pathways (Akt and ERK1/2) and inhibition of apoptotic MAPK pathway (JNK1).…”
Section: The Role Of Gsts In Rcc Progressionmentioning
confidence: 99%